2021
DOI: 10.3390/pathogens10091100
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Performing a Multivariate Optimization of Phage Production Using the RCCD Approach

Abstract: Bacteriophages can be used in various applications, from the classical approach as substitutes for antibiotics (phage therapy) to new biotechnological uses, i.e., as a protein delivery vehicle, a diagnostic tool for specific strains of bacteria (phage typing), or environmental bioremediation. The demand for bacteriophage production increases daily, and studies that improve these production processes are necessary. This study evaluated the production of a T4-like bacteriophage vB_EcoM-UFV09 (an E. coli-infectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 82 publications
0
8
1
Order By: Relevance
“…There is very little information published on the optimization of key process variables for phage production. The rotatable central composite design (RCCD) methodology was used, combining and comparing all parameters to determine the ideal conditions for the production process of bacteriophages [37]. Directly influenced by environmental conditions like medium composition, temperature, pH, and agitation [38,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…There is very little information published on the optimization of key process variables for phage production. The rotatable central composite design (RCCD) methodology was used, combining and comparing all parameters to determine the ideal conditions for the production process of bacteriophages [37]. Directly influenced by environmental conditions like medium composition, temperature, pH, and agitation [38,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Phage infection and development are determined by bacterial host factors such as nutritional state (Li et al, 2003 ). A recent study showed that carbon source is an important factor in phage production (Silva et al, 2021 ). A previous study using Bacillus subtilis showed that phage 29 infection downregulated CcpA‐dependent genes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the prevalence of antibiotic resistance, studies have been carried out using both standalone phage therapy and combinations of phages and antibiotics to treat bacterial infections in humans and other animals 1 8 . However, for phage therapy to become more realistic on a global scale, efficient strategies to mass produce phages need to be established 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering infection conditions, infection load (the amount of bacterial culture added in percent volume/volume) and MOI (ratio of infectious phages to viable bacterial cells) influence phage-host dynamics and the number of infection cycles that take place over the course of production 9 , 20 , 21 . An intermediate MOI may delay lysis, thereby allowing bacterial hosts to continue producing phages; in contrast an overly high or low MOI, results in rapid lysis or unimpeded bacterial growth respectively, sacrificing phage titer 14 , 15 , 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation